1993
DOI: 10.1083/jcb.121.3.631
|View full text |Cite
|
Sign up to set email alerts
|

Mouse notch: expression in hair follicles correlates with cell fate determination.

Abstract: Abstract. Many vertebrate tissues, including skin, are known to develop as a consequence of epithelialmesenchymal interactions. Much less is known about the role of cell-cell interaction within the epithelial or the mesenchymal compartments in morphogenesis. To investigate cell-cell interactions during skin development, and the potential role of the Notch homolog in this process, we cloned the mouse homolog of Notch (mNotch) and studied its expression pattern, starting as early as mesoderm formation. The novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 41 publications
1
89
0
3
Order By: Relevance
“…The Notch1 probe K was excised from the KS-Motch plasmid (Kopan and Weintraub, 1993). The Notch1 probe J is a 560 bp NcoI ± NcoI fragment of pMN7 (Reaume et al, 1992).…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Notch1 probe K was excised from the KS-Motch plasmid (Kopan and Weintraub, 1993). The Notch1 probe J is a 560 bp NcoI ± NcoI fragment of pMN7 (Reaume et al, 1992).…”
Section: Cellsmentioning
confidence: 99%
“…Z11886; (Del Amo et al, 1993)). Mutant A was constructed by ligating a BamHI ± BclI fragment of pMN7 (nt 5051 ± nt 5553) (Reaume et al, 1992) with a BclI-EcoRI fragment of pKS Motch (nt 5553 ± nt 8064) (Kopan and Weintraub, 1993). Mutant B (DCys) was deleted of the Nterminal part to the SspI site (nt 5187).…”
Section: Cellsmentioning
confidence: 99%
“…In Xenopus, expression of a gain-of-function truncated mutant (harboring only the intracellular domain) of X-Notch affects normal development (Coffman et al 1993) and prevents retinal cell differentiation (Dorsky et al 1995). In mammals, three Notch-related genes have been identified: Notchl, Notch2, and Notch3 (Ellisen et al 1991;Weinmaster et al 1991;Del Am• et al 1992;Reaume et al 1992;Weinmaster et al 1992;Lardelli and Lendahl 1993;Kopan and Weintraub 1993;Lardelli et al 1994), and Notchl also appears to control cell-fate determination (Kopan and Weintraub 1993;Kopan et al 1994;Nye et al 1994). Recent studies have shown that Notch signaling pathways have been preserved from Drosophila to mammals and involve binding to the CBF-1/RBP-JK trans-activator (Hsieh and Hayward 1995;Jarriault et al 1995).…”
mentioning
confidence: 99%
“…The Notch signaling pathway is also important for determining cell fate in HF development [87]. Notch signaling acts by blocking cell differentiation, which maintains the competence of undifferentiated cells [88,89] in both the developing tooth and the HF to respond to inductive signals that determine their developmental fate [87,90].…”
Section: Molecular Control Of Hair Follicle Development and Cyclingmentioning
confidence: 99%
“…Notch signaling acts by blocking cell differentiation, which maintains the competence of undifferentiated cells [88,89] in both the developing tooth and the HF to respond to inductive signals that determine their developmental fate [87,90]. Based on expression studies in the HF, Notch may be a competence factor, as its pattern of expression in the HF appears to be restricted to cells that have left the proliferative pool but have yet to terminally differentiate [91,92].…”
Section: Molecular Control Of Hair Follicle Development and Cyclingmentioning
confidence: 99%